IMPROVING THE STUDENTS’ READING COMPREHENSION ON DESCRIPTIVE TEXT THROUGH JIGSAW TEACHING STRATEGY - Ratmini Ratmini; Indawan Syahri; Baginda Simaibang (Universitas PGRI Palembang, 2020)
The research was based on a preliminary study on the problems related to student reading comprehension. The problems of the study were (1) students have little understanding to convey the meaning of words in the descriptive text, (2) long sentences in the descriptive text make students confused in understanding the meaning of the text, (3) students have a little interest in learning and understanding the meaning of the text, (4) teachers have difficulties to find the suitable method to stimulate students in learning reading text. This study was a classroom action research for the seventh-grade students of SMP Negeri 2 TelukGelam of OKI and its inquiry to improve student's reading comprehension on the descriptive text through jigsaw teaching strategy. This research was conducted in two cycles, each cycle has four steps these are (1) plan, (2) action, (3) observation, and (4) reflection. To collect the data, the researcher used the instrument of observations and tests. The data obtained were presented in two ways, qualitatively and quantitatively. The findings showed that there was an increasing average score from cycle 1 (61.60) to cycle 2 (83.75). It means that was 22.15% of students improving their reading ability to cycle 2. Based on the result, it is concluded that the jigsaw teaching strategy can improve students’ reading comprehension of the descriptive text in cycle 1 to cycle 2.